INCOME AND FEASIBILITY ANALYSIS OF PATCHOULI FARMING IN PASIE RAJA DISTRICT, SOUTH ACEH REGENCY: ANALISIS PENDAPATAN USAHATANI NILAM DI KECAMATAN PASIE RAJA KABUPATEN ACEH SELATAN - Khairun Nisa; Agustiar; Liston Siringo Ringo; Erlisa (ROCE : Jurnal Pertanian Terapan, 2026)
Patchouli farming is an important smallholder activity in South Aceh, but its profitability is vulnerable to price volatility, traditional cultivation practices, and high labor requirements. This study aimed to analyze the income, economic feasibility, and break-even point of patchouli farming in Pasie Raja District, South Aceh Regency. The research site was selected purposively because Pasie Raja is one of the patchouli-producing areas in South Aceh. A descriptive quantitative approach was applied using census data from 37 active patchouli farmers in five villages: Pucok Krueng, Ladang Teungoh, Panton Bili, Ladang Tuha, and Rambong. Primary data were collected through field observation, structured interviews, questionnaires, and documentation, while secondary data were obtained from relevant institutions and literature. The data were analyzed using total cost, total revenue, farm income, revenue-cost ratio, break-even production, and break-even price. The results showed that the average total production cost was IDR 8,412,694 per planting season, while average revenue reached IDR 15,315,237. The average farm income was IDR 7,578,294 per planting season. The revenue-cost ratio was 1.82, indicating that patchouli farming was financially feasible. The break-even production was 14.752 kg, below the actual average production of 26 kg, and the break-even price was IDR 317,535/kg, below the observed average selling price of IDR 570,270/kg. These findings suggest that patchouli farming in Pasie Raja remains profitable under current production and price conditions. However, its sustainability requires improved production efficiency, better distillation performance, stronger market access, and risk management against price volatility.